Slovenščina kot učni jezik in jezik sporazumevanja v slovenskem šolstvu - Jesenšek, Marko (Slavia Centralis, 2020)
Slovene as language of instruction and language of communication in Slovene educationThe article discusses the influence of Germanization, Illyrism, Yugo-Slovene movement and Anglicisation on Slovene language of instruction. Ivan Cankar’s view on the use of foreign language of instruction in the field of education is discussed, along with the current state of Slovene higher education, following the 2016 rejection of an amendment of the article in Higher Education Act, which proposed English to be recognised as a supplementary language of instruction on Slovene universities. Cankar’s indirect message to the Slovene university elite is that of the importance of the use of the mother tongue as the language of instruction, and that of Slovene as a language with a future. The term internationalization is often used to camouflage efforts to further expand the use of English in Slovenian universities.
Keywords: Slovene language of instruction; university; communication; Germanization; Illyrism; Yugo-Slovene movement; Anglicisation